Short-Term Effects of Biogas Digestates and Pig Slurry Application on Soil Microbial Activity - J. Abubaker; K. Risberg; E. Jönsson; A. S. Dahlin; H. Cederlund; M. Pell (Applied and Environmental Soil Science)
The effect of four biogas digestates (BD-A, BD-B, BD-C, and BD-D) and pig slurry (PS) on soil microbial functions was assessed at application rates corresponding to 0–1120 kg NH4+-N ha−1. At dose corresponding to 140 kg NH4+-N ha−1, 30.9–32.5% of the carbon applied in BD-A, BD-C, and PS was utilized during 12 days, while for BD-B and BD-D corresponding utilization was 19.0 and 16.9%, respectively. All BDs resulted in net nitrogen assimilation at low rates (17.5–140 kg NH4+-N ha−1) but net mineralization dominated at higher rates. PS resulted in net mineralization at all application rates. All residues inhibited potential ammonium oxidation (PAO), with EC50-values ranging between 45 and 302 kg NH4+-N ha−1. Low rates of BDs appeared to weakly stimulate potential denitrification activity (PDA), while higher rates resulted in logarithmic decrease. The EC50-values for PDA were between 238 and 347 kg NH4+-N ha−1. No inhibition of PDA was observed after amendment with PS. In conclusion, biogas digestates inhibited ammonia oxidation and denitrification, which could be an early warning of potential hazardous substances in the digestates. However, this effect can also be regarded as positive, since it may reduce nitrogen losses.